A biodegradable medical magnesium alloy and preparation method thereof

By adding zinc, manganese, carbon or zirconium to the magnesium alloy and using specific preparation methods, a new type of degradable medical magnesium alloy was developed, which solved the permanent existence of existing medical implantable metal materials in the human body. The problem is that the mechanical strength and corrosion resistance of magnesium alloy have been improved, and it is suitable for degradable implantable equipment for medical purposes.

CN116024472BActive Publication Date: 2025-02-14SHANGHAI BAIYUE MEDICAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310085726.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-09
Publication Date
2025-02-14
Estimated Expiration
2043-02-09

AI Technical Summary

Technical Problem

The existing medical implantable metal materials are permanently present in the human body due to their corrosion resistance, which have problems such as the risk of secondary surgery and postoperative inflammatory response, and their mechanical properties are not sufficient to meet the needs of certain medical uses.

Method used

Develop a new type of degradable medical magnesium alloy. By adding zinc, manganese, carbon or zirconium to the magnesium alloy, the mechanical strength and corrosion resistance of the alloy are optimized, and specific preparation methods such as smelting, cleaning and mechanical processing are adopted. , magnesium alloy materials with optimized fine grain and mechanical properties were prepared.

Benefits of technology

The mechanical strength and corrosion resistance of magnesium alloys have been improved, making them more suitable for degradable implantable equipment for medical purposes, reducing the risk of secondary surgery and the possibility of postoperative inflammatory response.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116024472B_ABST
    Figure CN116024472B_ABST
Patent Text Reader

Abstract

The present invention relates to a degradable medical magnesium alloy and a preparation method thereof, wherein the magnesium alloy comprises 1.0-2.5wt% zinc, 0.05-0.30wt% manganese, 0.05-0.40wt% carbon or zirconium, and unavoidable impurity elements, and the remaining components are magnesium. The preparation method of the magnesium alloy comprises the following steps: (1) smelting magnesium (2) adding carbon or zirconium (magnesium-zirconium alloy or zirconium chloride) (3) primary purification (4) adding zinc and manganese (5) filtering and cleaning (6) precipitation and standing (7) casting (8) melt heat treatment (9) machining. The carbon in the magnesium alloy component of the present invention is one of the essential elements for the human body, and its density is close to that of pure magnesium. Adding carbon to the magnesium alloy can play a role in refining the grains, thereby enhancing the mechanical strength and ductility of the magnesium alloy. Zirconium can also replace carbon. The present invention can prepare a magnesium alloy block material with an average grain diameter of less than 4μm, and has the mechanical strength and corrosion resistance required for degradable medical magnesium alloys, laying a material science foundation for fine and absorbable magnesium alloy medical devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of biomedical metal materials and production technologies thereof, and in particular to a novel biodegradable medical magnesium alloy and a preparation method thereof. Background Art

[0002] At present, the main medical implantable metal materials widely used in medicine include stainless steel, titanium alloy, cobalt-chromium alloy, etc. These materials have excellent strength and corrosion resistance. However, their corrosion resistance also means that these metal materials will remain in the human body permanently. For secondary surgeries that need to remove medical devices after healing and medical devices that are difficult to remove, there are many risks and hidden dangers such as the risk of secondary surgery and late postoperative inflammatory reactions, as well as difficulty in restoring the original normal physiological condition.

[0003] In order to solve the above-mentioned defects of existing implantable medical devices, materials that can be degraded and easily absorbed in the human body have received widespread attention. Among these materials, experts have great expectations for magnesium and magnesium alloys for the following reasons: (1) Magnesium is a major element necessary for the human body, is not prone to poisoning, and is relatively safe in the human body; (2) Compared with non-degradable medical metals, magnesium has a lower Young's coefficient and can effectively reduce stress shielding; (3) Compared with materials such as polylactic acid, magnesium and magnesium alloys have better mechanical properties.

[0004] The commercial use of magnesium alloys has a history of nearly 100 years, and most of them are magnesium-aluminum alloys in industry. By adding carbon to magnesium-aluminum alloys, it can play a role in reducing the grain size of the alloy and enhancing the mechanical properties. The academic community has long believed that these effects can only be produced in magnesium alloys containing aluminum. In the past two decades, studies have shown that adding carbon to pure magnesium, magnesium-zinc and other alloys can also play a similar role in enhancing the performance of magnesium alloy materials.

[0005] For degradable medical magnesium alloys, experts have always had doubts about the relationship between aluminum and Alzheimer's disease or senile dementia in terms of its impact on the human body, and long-term research has not yet reached a negative conclusion. Therefore, it is necessary to explore and study new degradable medical magnesium alloy component materials and their production methods without aluminum in the case of magnesium alloys that are used commercially in large quantities, using low-cost carbon elements, so that they can be optimized in terms of alloy grain refinement, enhanced mechanical properties and corrosion resistance, so as to achieve better processing and production of degradable magnesium alloy fine implants suitable for various medical purposes. Summary of the invention

[0006] The purpose of the present invention is to provide a new type of biodegradable medical magnesium alloy and a preparation method thereof, so as to overcome the deficiencies existing in the above-mentioned existing magnesium alloy materials and preparation technologies, and to improve the mechanical strength and corrosion resistance required for the biodegradable medical magnesium alloy.

[0007] To achieve the above object, the technical solution of the present invention is a novel biodegradable medical magnesium alloy, characterized in that:

[0008] The magnesium alloy includes 1.0-2.5 wt % of zinc (Zn), 0.05-0.30 wt % of manganese (Mn), 0.05-0.40 wt % of carbon (C) or zirconium (Zr), and inevitable impurity elements, and the remainder is magnesium (Mg).

[0009] In the above technical solution, the impurity elements include iron (Fe), copper (Cu) and nickel (Ni), wherein Fe≤0.004wt%, preferably≤0.002wt%; Cu≤0.002wt%, preferably≤0.001wt%; Ni≤0.001wt%, preferably≤0.0005wt%.

[0010] In the above technical solution, in the magnesium alloy, the weight percentages of Mg, Zn, Mn, C or Zr are respectively:

[0011] 98.90 (Mg), 1.0 (Zn), 0.05 (Mn), 0.05 (C or Zr);

[0012] 98.75 (Mg), 1.0 (Zn), 0.05 (Mn), 0.20 (C or Zr);

[0013] 98.60 (Mg), 1.0 (Zn), 0.05 (Mn), 0.35 (C or Zr);

[0014] 98.77 (Mg), 1.1 (Zn), 0.08 (Mn), 0.05 (C or Zr);

[0015] 97.43(Mg),2.2(Zn),0.14(Mn),0.23(C or Zr).

[0016] The method for preparing the biodegradable medical magnesium alloy in the above technical solution comprises the following steps and conditions:

[0017] Step 1: Smelting of Mg:

[0018] After pure Mg is cut into any shape, it is cleaned with acid or cut to remove the natural oxide film on the surface. When acid cleaning is performed, the surface of the ingot and the concave and convex parts of the cast pipe may not be sufficiently removed. Therefore, it is preferred to use the cutting method for treatment. Under the condition of inert gas or flameproof gas filling, the pretreated Mg is loaded into the smelting furnace to be completely melted, and the molten alloy temperature is maintained at 660-690°C.

[0019] Step 2: Addition of C or Zr:

[0020] Add C, inject C together with protective gas into the molten metal at a position where the precipitated impurities and inclusions will not be rolled up due to convection, wherein the C is C powder (carbon powder) with a particle size of less than 1 μm, and the temperature of the molten alloy is maintained at 660-690°C;

[0021] Alternatively, adding Mg-Zr alloy or ZrCl 4 , stirring after adding, so that the added material melts and the molten metal composition is homogenized; when ZrCl is added 4 When removing the slag floating on the surface of the molten metal, the chlorine gas is removed at the same time, and the temperature of the molten alloy is maintained at 660-690℃;

[0022] Step 3: Primary cleaning:

[0023] Through the following methods: 1) Add smelting flux and stir the molten metal. When slag is observed at the bottom of the furnace, use a mold to remove it; 2) Appropriately reduce the pressure in the furnace and inject protective gas into the lower part of the melting furnace. When using argon (Ar), the finer the bubbles, the better. The appropriate flow rate of inert gas should be changed according to the shape of the mold used to remove the slag floating on the surface of the molten metal. The duration and number of operations of this process should be changed according to the amount of molten metal and the cleanliness of the raw materials, until no slag is generated on the surface of the molten metal and the temperature of the molten alloy is maintained at 660-690℃;

[0024] Step 4: Addition of Zn and Mn:

[0025] Add Zn and Zn-Mn alloy, in which Mn is less than 10% by weight, and stir after adding to make the added material melt and the molten metal composition uniform, and the temperature of the molten alloy is maintained at 660-690°C;

[0026] Step 5: Filtration and purification:

[0027] After the molten metal is moved from the smelting furnace to the holding furnace, it is passed through a filter. The molten metal filter is a mesh or porous structure, and should be made of a material that does not react with the molten metal. After the primary purification process, larger inclusions have been removed, so an appropriate filter mesh size of 40 - 1,000 μm is appropriate. The mesh size selected for each operation should be adjusted according to the furnace structure, raw materials and primary purification process. Multiple filters can also be used in combination as needed. The molten alloy temperature is maintained at 660-690°C;

[0028] Step 6: Settle and let stand:

[0029] The filtered molten metal is allowed to stand for a period of 10-30 minutes to allow the impurities and inclusions to settle at the bottom of the furnace. The temperature of the molten alloy is maintained at 660-690°C.

[0030] Step 7: Casting:

[0031] The molten alloy is poured into an iron casting coated with a mold release agent to obtain a cylindrical ingot billet block. Preferably, it is preferably cast in a semi-continuous casting method or a metal mold using a water-cooled casting mold. If other casting methods that take a long time to complete solidification are selected, in order to prevent the precipitation or segregation of the micronized elements, a device for flowing the molten metal should be used, specifically electromagnetic stirring, vibration stirring or mechanical stirring above the solidification interface;

[0032] Step 8, melt heating treatment: place the casting block in an electric furnace with an ambient temperature of 320-420°C, take it out after standing for 1-48 hours, and then cool it with water;

[0033] Step nine: Mechanical processing: The specific method of mechanical processing includes at least one of extrusion, rolling, forging and drawing.

[0034] In the above magnesium alloy preparation method, the purity of Mg is above 3N, and the purity of Zn is above 4N.

[0035] In the above-mentioned magnesium alloy preparation method, the extrusion method conditions in step nine are as follows: the temperature is 200-400°C, preferably 300-350°C; the extrusion ratio is 5-150, preferably 20-80; the profile extrusion speed is 0.1-30 mm / sec., preferably 5-10 mm / sec.; the cooling method of the extruded material is preferably indirect or direct water cooling; the earlier the cooling start time, the better; preferably, a vertical extruder with downward extrusion mode is used, and a cooling water spray device after the casting mold is provided for direct water cooling treatment.

[0036] In the above-mentioned magnesium alloy preparation method, the rolling method described in step nine is to perform rough rolling, intermediate rolling and finish rolling in sequence, the rough rolling is performed at a temperature of 200-400°C, and the rolling reduction is 5-15%, the intermediate rolling is performed at a temperature of 350-400°C, and the rolling reduction is 20-50%, and the finish rolling is performed at a temperature of 200-300°C, and the rolling reduction is 5-10%.

[0037] In the above-mentioned magnesium alloy preparation method, the conditions of the forging method described in step nine are: forging temperature is 250-450°C, forging speed is 200-800 mm / sec., and forging rate is 15-50%.

[0038] In the above-mentioned magnesium alloy preparation method, the conditions of the drawing method described in step nine are that the drawing temperature is room temperature-300°C, the section reduction rate (Reduction of area) is 5-25%, and the annealing heat treatment conditions after drawing are temperature 300-380°C and time 10-30 minutes. The optimal conditions vary depending on the outer diameter of the material and the section reduction rate.

[0039] In the above-mentioned magnesium alloy preparation method, tools that are in direct contact with the molten alloy, such as the smelting crucible, dross-out fixture, and stirring fixture, should be made of a material that does not cause the Mg molten alloy components to dissolve.

[0040] Type of release agent: You can also use a release agent as needed. You should choose a type that will not fall off due to contact with raw materials, fixtures, or thermal shock and mix into the molten alloy.

[0041] The characteristics and positive effects of the present invention are:

[0042] First, the present invention excludes the aluminum element and adds carbon or zirconium to the magnesium, zinc and manganese elements. The non-metallic carbon (C) element is one of the essential elements for the human body, and its density is close to that of pure magnesium. Adding carbon to magnesium alloys can refine the grains, thereby enhancing the mechanical strength and elongation of magnesium alloys. Zirconium (Zr) has low in vitro ion toxicity and good in vivo biocompatibility, degradability, non-mutagenicity and carcinogenicity. Adding Zr to magnesium alloys can also be used as a grain refiner to refine the grain particles of magnesium alloys, improve the toughness and corrosion resistance of magnesium alloys, and play a similar role to the non-metallic element carbon (C).

[0043] Secondly, the magnesium alloy preparation method of the present invention obtains optimized micro-crystals under specific preparation conditions and processes.

[0044] The magnesium alloy material prepared by the present invention has the advantages of small size, mechanical strength and corrosion resistance, making it a new type of medical degradable magnesium alloy material. In addition, since the components of medical devices are relatively small, in order to adapt them to the production of fine and small-sized products, the magnesium alloy component material prepared by the present invention has both fine and small size and mechanical processing formability.

[0045] Thirdly, on the basis of smelting, the magnesium alloy of the present invention is prepared into a fine-grained magnesium alloy block material with an average grain diameter of less than 4μm through secondary purification and extrusion, rolling, forging, drawing and other steps, thereby obtaining optimized mechanical strength and corrosion resistance of the biodegradable medical magnesium alloy, laying a materials science foundation for further manufacturing fine and absorbable magnesium alloy medical devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 is a SEM image of the extruded material of Example 1.

[0047] Figure 2 This is a SEM image of the extruded material of Example 2.

[0048] Figure 3 This is a SEM image of the extruded material of Example 3.

[0049] Figure 4 This is a SEM image of the extruded material of Example 4.

[0050] Figure 5 This is a SEM image of the extruded material of Comparative Example 1.

[0051] Figure 6 This is a SEM image of the extruded material of Comparative Example 2.

[0052] Figure 7 The following are the results of corrosion resistance tests of Examples and Comparative Examples.

[0053] Figure 8 This is the grain map of the extruded material of Example 1.

[0054] Fig. 9 This is the grain map of the extruded material of Comparative Example 1. DETAILED DESCRIPTION

[0055] The present invention can be implemented through the following specific embodiments.

[0056] Embodiment 1,

[0057] The chemical composition of the magnesium alloy material of this embodiment is as follows by weight percentage: Zn 1.0 weight percent, Mn 0.05 weight percent, C 0.05 weight percent. Impurity elements that are inevitable in production include Fe, Cu, and Ni, among which Fe is less than 0.002 weight percent, Cu is less than 0.001 weight percent, and Ni is less than 0.0005 weight percent. The total content of impurity elements is less than 0.10 weight percent, and the remaining component is Mg.

[0058] Specified raw materials: pure Mg (3N), pure Zn (4N), Zn-Mn alloy (Mn: 9 wt%), and C powder (carbon powder) with a particle size of less than 1 μm.

[0059] Preparation steps and conditions of this embodiment:

[0060] (1) Melting of pure Mg: Only the pre-treated pure Mg is loaded into the melting furnace to be completely melted. The molten metal temperature is 660-680℃. The protective atmosphere is filled with inert gas.

[0061] (2) Addition of C: C and inert gas argon are injected into the lower part of the melting furnace at a position where the precipitated impurities and inclusions will not be rolled up due to convection. The temperature of the molten alloy is maintained at 660-680℃.

[0062] (3) Primary cleaning: Add the flux for smelting and stir it. When slag is produced at the bottom of the furnace, use a mold to remove it; appropriately reduce the pressure in the furnace, inject the protective gas into the lower part of the smelting furnace, and remove the slag floating to the surface of the molten metal. The temperature of the molten alloy is maintained at 660-680℃.

[0063] (4) Addition of Zn and Mn: Add Zn and Zn-Mn alloy, and stir after adding to make the added materials melt and the molten alloy composition uniform. The molten alloy temperature is maintained at 660-680℃.

[0064] (5) Filtration and purification: After the molten metal is moved from the smelting furnace to the holding furnace, it is passed through a mesh filter with a pore size of 50 μm.

[0065] (6) Settling: The molten alloy is allowed to settle to allow impurities and inclusions to settle at the bottom of the furnace.

[0066] The temperature is maintained at 660-680°C and the precipitation standing time is 10 minutes.

[0067] (7) Casting: The molten alloy is poured into an iron casting coated with a release agent to obtain a cylindrical ingot billet block.

[0068] (8) Melt heating treatment: Place the cast block in an electric furnace at an ambient temperature of 360°C, let it stand for 12 hours, then take it out and cool it with water.

[0069] (9) Extrusion processing: After the ingot block is cut to remove the skin, it is extruded at a temperature of 350°C and an extrusion ratio of

[0070] 120. The extrusion process is carried out at an extrusion speed of 7 mm / sec. to obtain an extruded sheet. A cooling water spray device is used for direct water cooling.

[0071] Embodiment 2,

[0072] The chemical composition of the magnesium alloy material of this embodiment is as follows by weight percentage: Zn 1.0 weight percent, Mn 0.05 weight percent, Zr 0.05 weight percent, and impurity elements that are inevitable in production include Fe, Cu, and Ni, among which Fe is less than 0.002 weight percent, Cu is less than 0.001 weight percent, and Ni is less than 0.0005 weight percent. The total content of impurity elements is less than 0.10 weight percent, and the remaining component is Mg.

[0073] Designation of raw materials: pure Mg (3N), pure Zn (4N), Zn-Mn alloy (Mn: 9 wt%), Mg-Zr alloy (Zr: 30 wt%).

[0074] Preparation steps and conditions of this embodiment:

[0075] (1) Melting of pure Mg: Only the pre-treated pure Mg is loaded into the melting furnace to be completely melted. The molten metal temperature is 660-680℃. The protective atmosphere is filled with inert gas.

[0076] (2) Addition of Zr: Add Mg-Zr alloy and stir it after adding to make the added material melt and the molten alloy composition uniform. The molten alloy temperature is 660-680℃.

[0077] (3) Primary cleaning: Add the flux for smelting and stir it. When slag is produced at the bottom of the furnace, use a mold to remove it; appropriately reduce the pressure in the furnace, inject the protective gas into the lower part of the smelting furnace, and remove the slag floating to the surface of the molten metal. The temperature of the molten alloy is maintained at 660-680℃.

[0078] (4) Addition of Zn and Mn: Add Zn and Zn-Mn alloy, and stir after adding to make the added materials melt and the molten alloy composition uniform. The molten alloy temperature is 660-680℃.

[0079] (5) Filtration and purification: After the molten metal is moved from the smelting furnace to the holding furnace, it is passed through a mesh filter with a pore size of 50 μm.

[0080] (6) Settling: The molten alloy is allowed to settle to allow impurities and inclusions to settle at the bottom of the furnace. The temperature of the molten alloy is maintained at 660-680°C and the settling time is 20 minutes.

[0081] (7) Casting: The molten alloy is poured into an iron casting coated with a release agent to obtain a cylindrical ingot billet block.

[0082] (8) Melt heating treatment: Place the ingot billet in an electric furnace at an ambient temperature of 360°C, let it stand for 12 hours, then take it out and cool it with water.

[0083] (9) Extrusion: After the ingot billet is cut to remove the skin, it is extruded at an extrusion temperature of 350°C, an extrusion ratio of 120, and an extrusion speed of 7 mm / sec to obtain an extruded sheet. The cooling method of the extruded material is the same as in Example 1.

[0084] Embodiment 3,

[0085] The chemical composition of the magnesium alloy material of this embodiment is as follows by weight percentage: Zn 2.4 wt%, Mn 0.11 wt%, C 0.2 wt%. Impurity elements inevitable in production include Fe, Cu, and Ni, among which Fe is less than 0.002 wt%, Cu is less than 0.001 wt%, and Ni is less than 0.0005 wt%. The total content of impurity elements is less than 0.10 wt%, and the remaining component is Mg.

[0086] Specified raw materials: pure Mg (3N), pure Zn (4N), Zn-Mn alloy (Mn: 9 wt%), and C powder (carbon powder) with a particle size of less than 1μm.

[0087] Preparation steps and conditions of this embodiment:

[0088] (1) Melting of pure Mg: Only the pre-treated pure Mg is loaded into the melting furnace to be completely melted. The molten metal temperature is 660-680℃. The protective atmosphere is filled with inert gas.

[0089] (2) Addition of C: C and inert gas are injected into the lower part of the melting furnace at a position where the precipitated impurities and inclusions will not be rolled up due to convection. The temperature of the molten alloy is maintained at 660-680℃.

[0090] (3) Primary cleaning: Add the flux for smelting and stir it. When slag is produced at the bottom of the furnace, use a mold to remove it; appropriately reduce the pressure in the furnace, inject the protective gas into the lower part of the smelting furnace, and remove the slag floating to the surface of the molten metal. The temperature of the molten alloy is maintained at 660-680℃.

[0091] (4) Addition of Zn and Mn: Add Zn and Zn-Mn alloy. Stirring is performed after addition to melt the added materials and homogenize the composition of the molten alloy. The temperature of the molten alloy is maintained at 660-680℃.

[0092] (5) Filtration and purification: After the molten metal is moved from the smelting furnace to the holding furnace, it is passed through a mesh filter with a pore size of 100 μm.

[0093] (6) Settling: The molten alloy is allowed to settle to allow impurities and inclusions to settle at the bottom of the furnace. The temperature of the molten alloy is maintained at 660-680°C and the settling time is 10 minutes.

[0094] (7) Casting: The molten alloy is poured into an iron casting coated with a release agent to obtain a cylindrical ingot billet block.

[0095] (8) Melt heating treatment: Place the cast block in an electric furnace at an ambient temperature of 360°C, let it stand for 12 hours, then take it out and cool it with water.

[0096] (9) Extrusion: After the ingot billet is cut to remove the skin, it is extruded at an extrusion temperature of 350°C, an extrusion ratio of 120, and an extrusion speed of 7 mm / sec to obtain an extruded sheet. The cooling method of the extruded material is the same as in Example 1.

[0097] Embodiment 4,

[0098] The chemical composition of the magnesium alloy material of this embodiment is as follows by weight percentage: Zn 2.4 weight percent, Mn 0.11 weight percent, Zr 0.2 weight percent, and unavoidable impurity elements in production include Fe, Cu, and Ni, among which Fe is less than 0.002 weight percent, Cu is less than 0.001 weight percent, and Ni is less than 0.0005 weight percent. The total content of impurity elements is less than 0.10 weight percent, and the remaining component is Mg.

[0099] Designation of raw materials: pure Mg (3N), pure Zn (4N), Zn-Mn alloy (Mn: 9 wt%), and zirconium chloride are selected.

[0100] Preparation steps and conditions of this embodiment:

[0101] (1) Melting of pure Mg: Only the pre-treated pure Mg is loaded into the melting furnace to be completely melted. The molten metal temperature is 660-680℃. The protective atmosphere is filled with inert gas.

[0102] (2) Addition of Zr: Adding zirconium chloride (ZrCl 4 ), and stir after adding to make the added material melt and the molten metal composition uniform. Remove the chlorine gas while removing the scum floating on the surface of the molten metal. The temperature of the molten metal is 660-680℃.

[0103] (3) Primary cleaning: Add the flux for smelting and stir it. When slag is produced at the bottom of the furnace, use a mold to remove it; appropriately reduce the pressure in the furnace, inject the protective gas into the lower part of the smelting furnace, and remove the slag floating to the surface of the molten metal. The temperature of the molten alloy is maintained at 660-680℃.

[0104] (4) Addition of Zn and Mn: Add Zn and Zn-Mn alloy, and stir after adding to make the added materials melt and the molten alloy composition uniform. The molten alloy temperature is 660-680℃.

[0105] (5) Filtration and purification: After the molten metal is moved from the smelting furnace to the holding furnace, it is passed through a mesh filter with a pore size of 100 μm.

[0106] (6) Settling: The molten alloy is allowed to settle to allow impurities and inclusions to settle at the bottom of the furnace. The temperature of the molten alloy is maintained at 660-680°C and the settling time is 30 minutes.

[0107] (7) Casting: The molten alloy is poured into an iron casting coated with a release agent to obtain a cylindrical ingot billet block.

[0108] (8) Melt heating treatment: Place the ingot billet in an electric furnace at an ambient temperature of 360°C, let it stand for 12 hours, then take it out and cool it with water.

[0109] (9) Extrusion: After the ingot billet is cut to remove the skin, it is extruded at an extrusion temperature of 350°C, an extrusion ratio of 120, and an extrusion speed of 7 mm / sec to obtain an extruded sheet. The cooling method of the extruded material is the same as in Example 1.

[0110] Comparative Example 1,

[0111] The chemical composition of the magnesium alloy material in this comparative example is as follows by weight percentage: Zn 1.0 wt%, Mn 0.05 wt%. Impurity elements that are inevitable in production include Fe, Cu, and Ni, among which Fe is 0.002 wt%, Cu is 0.001 wt%, and Ni is 0.0005 wt%. The total content of impurity elements is <0.10 wt%, and the remaining component is Mg.

[0112] Designation of raw materials: pure Mg (3N), pure Zn (4N), Zn-Mn alloy (Mn: 9 wt%) are selected.

[0113] Preparation steps and conditions of magnesium alloy in this comparative example:

[0114] (1) Melting of pure Mg: Only the pre-treated pure Mg is loaded into the melting furnace to be completely melted. The molten metal temperature is 660-680℃. The protective atmosphere is filled with inert gas.

[0115] (2) Primary cleaning: Add the flux for smelting and stir it. When slag is produced at the bottom of the furnace, use a mold to remove it; appropriately reduce the pressure in the furnace, inject the protective gas into the lower part of the smelting furnace, and remove the slag floating to the surface of the molten metal. The temperature of the molten alloy is maintained at 660-680℃.

[0116] (3) Addition of Zn and Mn: Add Zn and Zn-Mn alloy. Stirring is performed after addition to melt the added materials and homogenize the composition of the molten alloy. The temperature of the molten alloy is maintained at 660-680℃.

[0117] (4) Filtration and purification: After the molten metal is moved from the smelting furnace to the holding furnace, it is passed through a mesh filter with a pore size of 50 μm.

[0118] (5) Settling: The molten alloy is allowed to settle to allow impurities and inclusions to settle at the bottom of the furnace. The temperature of the molten alloy is maintained at 660-680°C and the settling time is 10 minutes.

[0119] (6) Casting: The molten alloy is poured into an iron casting coated with a release agent to obtain a cylindrical ingot billet.

[0120] (7) Melt heating treatment: Place the cast block in an electric furnace at an ambient temperature of 360°C, let it stand for 12 hours, then take it out and cool it with water.

[0121] (8) Extrusion: After the ingot billet is cut to remove the skin, it is extruded at an extrusion temperature of 350°C, an extrusion ratio of 120, and an extrusion speed of 7 mm / sec to obtain an extruded sheet. The cooling method of the extruded material is the same as in Example 1.

[0122] Comparative Example 2,

[0123] The chemical composition of the magnesium alloy material of this comparative example is as follows by weight percentage: Zn 2.4 wt%, Mn 0.11 wt%. Impurity elements that are inevitable in production include Fe, Cu, and Ni, among which Fe is 0.002 wt%, Cu is 0.001 wt%, and Ni is 0.0005 wt%. The total content of impurity elements is <0.10 wt%, and the remaining component is Mg.

[0124] Designation of raw materials: pure Mg (3N), pure Zn (4N), Zn-Mn alloy (Mn: 9 wt%) are selected.

[0125] Preparation steps and conditions of magnesium alloy in this comparative example:

[0126] (1) Melting of pure Mg: Only the pre-treated pure Mg is loaded into the melting furnace to be completely melted. The molten metal temperature is 660-680℃. The protective atmosphere is filled with inert gas.

[0127] (2) Primary cleaning: Add the flux for smelting and stir it. When slag is produced at the bottom of the furnace, use a mold to remove it; appropriately reduce the pressure in the furnace, inject the protective gas into the lower part of the smelting furnace, and remove the slag floating to the surface of the molten metal. The temperature of the molten alloy is maintained at 660-680℃.

[0128] (3) Addition of Zn and Mn: Add Zn and Zn-Mn alloy. Stirring is performed after addition to melt the added materials and homogenize the composition of the molten alloy. The temperature of the molten alloy is maintained at 660-680℃.

[0129] (4) Filtration and purification: After the molten metal is moved from the smelting furnace to the holding furnace, it is passed through a mesh filter with a pore size of 100 μm.

[0130] (5) Settling: The molten alloy is allowed to settle to allow impurities and inclusions to settle at the bottom of the furnace. The temperature of the molten alloy is maintained at 660-680°C and the settling time is 10 minutes.

[0131] (6) Casting: The molten alloy is poured into an iron casting coated with a release agent to obtain a cylindrical ingot billet.

[0132] (7) Melt heating treatment: Place the cast block in an electric furnace at an ambient temperature of 360°C, let it stand for 12 hours, then take it out and cool it with water.

[0133] (8) Extrusion: After the ingot billet is cut to remove the skin, it is extruded at an extrusion temperature of 350°C, an extrusion ratio of 120, and an extrusion speed of 7 mm / sec to obtain an extruded sheet. The cooling method of the extruded material is the same as in Example 1.

[0134] Result 1: Mechanical properties evaluation:

[0135] The mixing ratio of Mg:Zn:Mn:C (or Zr) (expressed in weight percentage) is:

[0136] 98.75,1.0,0.05,0.20(0.00),

[0137] 98.60,1.0,0.05,0.35(0.00),

[0138] 98.77,1.1,0.08,0.05(0.00),

[0139] 97.43,2.2,0.14,0.23(0.00),

[0140] 98.20,1.7,0.05,0.00(0.05),

[0141] 97.50,2.4,0.05,0.00(0.05),

[0142] 98.75,1.0,0.05,0.00(0.20),

[0143] 98.60,1.0,0.05,0.00(0.35),

[0144] 98.80,1.0,0.15,0.00(0.05),

[0145] 98.70,1.0,0.25,0.00(0.05).

[0146] The ingot billet block was prepared under the same smelting and casting conditions as in Example 1 or 2. The extrusion process was then performed, with an extrusion temperature of 330°C, an extrusion ratio of 30, and an extrusion speed of 6 mm / sec. According to the ASTM-E8 / E8M-09 tensile (stretching) test standard, the extruded material obtained was prepared into a tensile sample, and a tensile test was performed in the long axis direction, with a tensile speed of 0.05 mm / mm・min, and the number of samples per group was n=5. The average values ​​of the test results are shown in Table 1;

[0147]

[0148] The 0.2% yield strength and tensile strength are proportional to the content of Zn, Mn, C (or Zr), and can be adjusted by changing the content of the above elements.

[0149] According to the ASTM-E8 / E8M-09 tensile test standard, the extruded materials prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were prepared into tensile samples, and tensile tests were performed in the long axis direction at a tensile speed of 0.05 mm / mm·min. The number of samples per group was n=5, and the experimental results are shown in Table 2;

[0150]

[0151] The results show that adding C or Zr elements can effectively improve the mechanical properties of the alloy, and the effects of C and Zr elements are similar in mechanical properties.

[0152] Result 2: Metal structure analysis:

[0153] For Example 1-4 and Comparative Example 1-2, the ingot was cut into samples using a cutter. After mirror polishing, the samples were analyzed using SEM. Figure 1-6 As shown, the characteristic of the metal structure is that Zn and Mn are basically dissolved in the α-Mg matrix, so only the α-Mg matrix was observed and confirmed. The observed black spots are C, and the tiny white spots are compounds of Zn or Zr. According to the ASTM E112-96 standard test method for average grain size determination, the grain map of Example 1 and Comparative Example 1 was photographed under a microscope, and the grain size was determined using the planimetry method. The average grain diameter of Example 1 was measured and calculated to be 3μm, and the average grain diameter of Comparative Example 1 was 5.2μm. The grain map of Example 1 is shown in Figure 8 As shown, the grain map of Comparative Example 1 is as follows Fig. 9 shown.

[0154] Result 3: Corrosion resistance test

[0155] The materials of Examples 1-4 and Comparative Examples 1-2 were cut into thin plates using a precision cutting machine, and both sides were mirror-polished. The thin plate material was immersed in a mixed solution of EMEM: FBS: Penicillin (penicillin) at a ratio of 100:10:1, and the Mg dissolution amount after immersion for 1 day, 3 days, 7 days, 14 days, and 28 days was measured. The storage conditions were 37°C + CO25%, and the shaking was carried out at 100 rpm. The test results are shown in Table 3 and Figure 7 As shown;

[0156]

[0157] The effect of Zr on the metal structure of magnesium alloy is similar to that of C. Therefore, Zr can replace C. As shown in Tables 1 and 2, Zr and C show similar effects in improving mechanical properties. In addition, as shown in Tables 3 and Figure 7 As shown, the corrosion resistance of the two is also similar. Therefore, according to the design requirements of medical devices, different alloy composition combinations can be used to give material properties suitable for different medical devices and the processing and production requirements of the finished products.

[0158] The above embodiments are only the best embodiments of the present invention and have no limiting effect on the protection scope of the present invention. All non-substantial changes and adjustments made by technical practitioners in this professional field on the basis of the present invention are within the protection scope claimed by the present invention.

Claims

1. A biodegradable medical magnesium alloy, characterized in that: The magnesium alloy comprises 1.0-2.5 wt % zinc, 0.05-0.30 wt % manganese, and 0.05-0.40 wt % carbon; or 2.4 wt% zinc, 0.11 wt% manganese, 0.20 wt% zirconium, and inevitable impurity elements, the remainder being magnesium; Among them, the particle size of carbon powder in the raw material for synthesizing magnesium alloy is less than 1 μm.

2. The biodegradable medical magnesium alloy according to claim 1, characterized in that: The impurity elements include iron, copper and nickel, wherein Fe≤0.004 wt %; Cu≤0.002 wt %; and Ni≤0.001 wt %.

3. The biodegradable medical magnesium alloy according to claim 2, characterized in that: Fe≤0.002 wt%; Cu≤0.001 wt%; Ni≤0.0005 wt%.

4. A method for preparing a biodegradable medical magnesium alloy according to any one of claims 1 to 3, characterized in that : Step 1: Smelting of Mg: After pure Mg is cut into any shape, it is cleaned with acid or cut to remove the natural oxide film on the surface; under the condition of inert gas or flameproof gas filling, the pre-treated Mg is loaded into the melting furnace to make it completely melted, and the temperature of the molten alloy is maintained at 660-690℃; Step 2: Addition of C or Zr: Add C, inject C together with protective gas into the molten metal at a position where the precipitated impurities and inclusions will not be rolled up due to convection, wherein the C is C powder with a particle size of less than 1 μm, and the temperature of the molten alloy is maintained at 660-690°C; Alternatively, Mg-Zr alloy or ZrCl4 is added, and stirred after addition to make the added material melt and the molten metal composition uniform; when ZrCl4 is added, chlorine is removed while removing the scum floating to the surface of the molten metal, and the temperature of the molten alloy is maintained at 660-690°C; Step 3: Primary cleaning: Through the following methods: 1) Add smelting flux and stir the molten metal. When slag is observed at the bottom of the furnace, use a mold to remove it; 2) Appropriately reduce the pressure in the furnace and inject protective gas into the lower part of the smelting furnace. When using argon gas, the finer the bubbles, the better. Remove the slag floating on the surface of the molten metal. The duration and number of operations of this process should be changed according to the amount of molten metal and the cleanliness of the raw materials, until no slag is generated on the surface of the molten metal and the temperature of the molten alloy is maintained at 660-690℃; Step 4: Addition of Zn and Mn: Add Zn and Zn-Mn alloy, in which Mn is less than 10 wt % and stir after adding to make the added material melt and the molten metal composition uniform, and the temperature of the molten alloy is maintained at 660-690°C; Step 5: Filtration and purification: After the molten metal is moved from the smelting furnace to the holding furnace, it is passed through a filter. The molten metal filter is a mesh or porous structure, and the material that does not react with the molten metal should be selected. After the primary purification process, the larger inclusions have been removed. Therefore, the filter mesh size is selected to be 40-1,000μm. The mesh size selected for each operation should be adjusted according to the furnace structure, raw materials and primary purification process, or multiple filters can be used in combination as needed. The molten alloy temperature is maintained at 660-690℃; Step 6: Settle and let stand: The filtered molten metal is allowed to stand for a period of 10-30 minutes to allow the impurities and inclusions to settle at the bottom of the furnace. The temperature of the molten alloy is maintained at 660-690°C. Step 7: Casting: The molten alloy is poured into an iron casting coated with a mold release agent to obtain a cylindrical ingot billet block; Step 8: Melt heating treatment: The casting block is placed in an electric furnace with an ambient temperature of 320-420°C, and after being left to stand for 1-48 hours, it is taken out and then cooled with water; Step 9: Mechanical processing: The specific method of mechanical processing includes at least one of extrusion, rolling, forging and drawing.

5. A method for preparing a biodegradable medical magnesium alloy as claimed in claim 4, characterized in that: The purity of the Mg is 3N or higher, and the purity of the Zn is 4N or higher.

6. A method for preparing a biodegradable medical magnesium alloy as claimed in claim 4, characterized in that: In step nine, the conditions of the extrusion method are as follows: temperature of 200-400° C.; extrusion ratio of 5-150; profile extrusion speed of 0.1-30 mm / sec.; and cooling method of the extruded material is indirect or direct water cooling.

7. A method for preparing a biodegradable medical magnesium alloy as claimed in claim 6, characterized in that: In step nine, the conditions of the extrusion method are as follows: temperature of 300-350°C; extrusion ratio of 20-80; profile extrusion speed of 5-10 mm / sec.; and cooling method of the extruded material using a vertical extruder with downward extrusion mode, equipped with a post-mold cooling water spray device, for direct water cooling treatment.

8. A method for preparing a biodegradable medical magnesium alloy as claimed in claim 4, characterized in that: In step nine, the rolling method is to perform rough rolling, intermediate rolling and finish rolling in sequence, the rough rolling is carried out at a temperature of 200-400°C, with a pass reduction of 5-15%, the intermediate rolling is carried out at a temperature of 350-400°C, with a pass reduction of 20-50%, and the finish rolling is carried out at a temperature of 200-300°C, with a pass reduction of 5-10%.

9. A method for preparing a biodegradable medical magnesium alloy as claimed in claim 4, characterized in that: In step nine, the forging method is carried out under the following conditions: forging temperature is 250-450° C., forging speed is 200-800 mm / sec., and forging rate is 15-50%.

10. The method for preparing a biodegradable medical magnesium alloy according to claim 4, characterized in that: In step nine, the conditions of the drawing method are as follows: the drawing temperature is room temperature-300° C., the cross-sectional reduction rate is 5-25%, and the annealing heat treatment conditions after the drawing process are as follows: the temperature is 300-380° C., and the time is 10-30 minutes.

Citation Information

Patent Citations

  • Magnesium alloy melt multistage compound purification method

    CN103820665A

  • Bio-medical Mg-Zn-Zr-Mn magnesium alloy and preparation method thereof

    CN105256213A

  • Magnesium alloy

    CN111801435A